Effect of Organic Matter on the Behavior and Control Effectiveness of Herbicides in Soil - TAKESHITA,V. (2019)
ABSTRACT: With extensive use of herbicides in agricultural areas, the risk of contamination of groundwater and surface water by these products has become a worldwide concern. Practices of application or maintenance of soil organic residues that have begun to be used in agriculture for soil nutrition have demonstrated other benefits besides nutrient supplementation, such as reduced mobility and increased soil degradation of herbicides. Because it is the final destination of herbicides, soil and its constituents, especially organic matter in tropical soils, play a prominent role in processes that encompass the dynamics of herbicide molecules. In this context, it is necessary to know the influence of the organic matter and its constituents on the behavior of the herbicides. This review discusses the main relationships of organic matter in the retention, transport, and transformation processes of herbicides in the soil, as well as the interference in the weed control effectiveness of these products. Because of this, knowing the influence of organic matter in the various processes related to the behavior of herbicides in the soil allows us to adopt more appropriate management practices regarding both weed control and remediation of contaminated areas. However, despite the wide range of information on the subject in the literature, each situation is distinct due to the wide variation in the behavioral response of the products to the different types of organic material present in the soil.